2022
DOI: 10.1097/aog.0000000000004649
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-Associated Deaths Due to Drugs, Suicide, and Homicide in the United States, 2010–2019

Abstract: Count per 100,000 live births in that racial and ethnic group from 2010 to 2019. † Rate ratio5pregnancy-associated death ratio in group divided by pregnancy-associated death ratio in reference group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 29 publications
1
59
1
Order By: Relevance
“…Suicides were so numerous among young women with unwanted pregnancies in El Salvador that they became a leading cause of maternal mortality after a total abortion ban there (Moloney 2014;Teter 2020). Deaths by homicide nearly double during pregnancy and the postpartum period in the United States (Margerison et al 2022;Subbaraman 2021). We anticipate that the Dobbs decision will increase risks of both suicide and homicide for pregnant people.…”
Section: Suicide and Homicidementioning
confidence: 99%
“…Suicides were so numerous among young women with unwanted pregnancies in El Salvador that they became a leading cause of maternal mortality after a total abortion ban there (Moloney 2014;Teter 2020). Deaths by homicide nearly double during pregnancy and the postpartum period in the United States (Margerison et al 2022;Subbaraman 2021). We anticipate that the Dobbs decision will increase risks of both suicide and homicide for pregnant people.…”
Section: Suicide and Homicidementioning
confidence: 99%
“…For that reason, others have elected to broaden the definition of maternal mortality. A recent study by Margerison et al published earlier this year has evaluated all maternal deaths within 1 year of delivery, and from all causes has shown that approximately one fifth of maternal deaths are due to drug abuse, suicide or homicide 1. Broadening the definition of maternal mortality is very interesting and requires more study.…”
Section: Commentmentioning
confidence: 99%
“…Pregnancyassociated drug-related deaths are most common among those aged 35 years or older, whereas suicide and homicide were most common among the youngest birthing people. 25…”
Section: Race and Maternal Suicidementioning
confidence: 99%